Complex life histories predispose aphids to recent abundance declines. (3rd July 2021) - Crossley, Michael S.; Smith, Olivia M.; Davis, Thomas S.; Eigenbrode, Sanford D.; Hartman, Glen L.; Lagos‐Kutz, Doris; Halbert, Susan E.; Voegtlin, David J.; Moran, Matthew D.; Snyder, William E.
Abstract: Many animals change feeding habits as they progress through life stages, exploiting resources that vary in space and time. However, complex life histories may bring new risks if rapid environmental change disrupts the timing of these switches. Here, we use abundance times series for a diverse group of herbivorous insects, aphids, to search for trait and environmental characteristics associated with declines. Our meta dataset spanned three world regions and >300 aphid species, tracked at 75 individual sites for 10–50 years. Abundances were generally falling, with median changes of −8.3%, −5.6%, and −0.1% per year in the central USA, northwestern USA, and United Kingdom, respectively. Aphids that obligately alternated between host plants annually and those that were agricultural pests exhibited the steepest declines, relative to species able to persist on the same host plant year‐round or those in natural areas. This suggests that host alternation might expose aphids to climate‐induced phenology mismatches with one or more of their host plant species, with additional risks from exposure to insecticides and other management efforts. Warming temperatures through time were associated with milder aphid declines or even abundance increases, particularly at higher latitudes. Altogether, while a warming world appeared to benefit some aphid species in some places, most aphid species that had time‐sensitive movements among multiple host plants seemed to face greater risk of decline. More generally, this suggests that recent human‐induced rapid environmental change is rebalancing the risks and rewards associated with complex life histories. Abstract : Leveraging observations from aphid monitoring networks in three world regions that tracked >300 aphid species at 75 sites for 10–50 years, we found that declines in abundance were steepest among aphids that obligately alternate between host plants. Recent human‐induced rapid environmental change may be rebalancing the risks and rewards associated with complex life histories.